Реалізація естетичної функції прикметників у перекладному тексті - Петрик, О. М.; Сухомлін, А. А. (Видавництво НДУ ім.М. В. Гоголя, 2017)
У статті розглянуто проблему реалізації естетичної функції прикметників у перекладних поетичних текстах Б.-І. Антонича. Виявлено, що прикметники, репрезентуючи естетичну функцію в ролі зображально-виражальних засобів, відтворені як еквівален-тами, так і за допомогою різних видів трансформацій.
The article deals with the problem of realization of aesthetic function of adjectives in translated poetic texts based on poetry of B.-I. Antonych. It is found out that adjectives representing the aesthetic function in the role of epithets, oxymorones, components of comparisons are reproduced by equivalents and through various types of transformations. Replacements and permutations were the most commonly used, addition and omission – less commonly used. Individually there are compensations and antonymic translation.
Keywords: поетичний текст; естетична функція; прикметник; трансформація